Ética e trabalho: Concepção de uma antítese social - Inácio, José Reginaldo [UNESP] (2013)
Ethics and work are inseparable essence of mankind. They ontologically synthesize the integrity of man as an element that allows to observe it in their accomplishments or productions. In this thesis, we consider a Marxist theoretical basis. Texts of Marx and Engels themselves, other authors mainly Sánchez Vázquez and Lukács, besides Dussel, Barroco, Iasi, Heller, Carcova to situate ethics advocated here that, if confirmed, breaks the boundaries imposed by capitalism. Aiming to demonstrate if social and livelihoods conditions of workers, employed or unemployed influence the ethic conception and moral values of a society, the thesis was divided into six chapters, of which the introduction is the first. In the second, Conceptualization as a foundation in theory, we seek the fundamental aspects of the thesis, its conceptualization from the research object itself (ethics, work, conception, antithesis, and social). We highlight some thinkers like Aristotle and Kant, which are the bases of this concept and also highlight important elements of the other chapters, such as ethics and its relationship with the power and the law. In the third, Perspectives and methodological limitations of the research, we present the methodology (dialectics) by which the research was conducted. Also in this chapter, we present a critical analysis of research in Social Sciences and its practice, besides certain limits, contradictions and implications to certain requirements, such as the case of originality. In the fourth, Ethics and Society, we emphasize ethics as a social foundation, the main environments in which it is perceived and is essential to the concepts adopted until now. Conditions or circumstances that influence ethics, as attributes (virtues), behavior and needs, are also important parts of this chapter, which also discusses the power structures, the relationship between law and ethics and the implications of the...